The Role and Mechanism of ATM-Mediated Autophagy in the Transition From Hyper-Radiosensitivity to Induced Radioresistance in Lung Cancer Under Low-Dose Radiation - Wang, Qiong; Chen, Yangyang; Chang, Haiyan; Hu, Ting; Wang, Jue; Xie, Yuxiu; Cheng, Jing (Frontiers in Cell and Developmental Biology, 2021)
Objective: This study aimed to investigate the effect of ataxia telangiectasia mutated (ATM)–mediated autophagy on the radiosensitivity of lung cancer cells under low-dose radiation and to further investigate the role of ATM and its specific mechanism in the transition from hyperradiosensitivity (HRS) to induced radioresistance (IRR). Methods: The changes in the HRS/IRR phenomenon in A549 and H460 cells were verified by colony formation assay. Changes to ATM phosphorylation and cell autophagy in A549 and H460 cells under different low doses of radiation were examined by western blot, PCR, and electron microscopy. ATM expression was knocked down by short interfering RNA (siRNA) transfection, and ATM-regulated molecules related to autophagy pathways were screened by transcriptome sequencing analysis. The detection results were verified by PCR and western blot. The differential metabolites were screened by transcriptome sequencing and verified by colony formation assay and western blot. The nude mouse xenograft model was used to verify the results of the cell experiments. Results: (1) A549 cells with high expression of ATM showed positive HRS/IRR, whereas H460 cells with low expression of ATM showed negative HRS/IRR. After the expression of ATM decreased, the HRS phenomenon in A549 cells increased, and the radiosensitivity of H460 cells also increased. This phenomenon was associated with the increase in the autophagy-related molecules phosphorylated c-Jun N-terminal kinase (p-JNK) and autophagy/Beclin 1 regulator 1 (AMBRA1). (2) DL-Norvaline, a product of carbon metabolism in cells, inhibited autophagy in A549 cells under low-dose radiation. DL-Norvaline increased the expression levels of ATM, JNK, and AMBRA1 in A549 cells. (3) Mouse experiments confirmed the regulatory role of ATM in autophagy and metabolism and its function in HRS/IRR. Conclusion: ATM may influence autophagy through p-JNK and AMBRA1 to participate in the regulation of the HRS/IRR phenomenon. Autophagy interacts with the cellular carbon metabolite DL-norvaline to participate in regulating the low-dose radiosensitivity of cells.